Integrating energy access, efficiency and renewable energy policies in sub-Saharan Africa: a model-based analysis. (14th December 2020) - Dagnachew, Anteneh G; Poblete-Cazenave, Miguel; Pachauri, Shonali; Hof, Andries F; van Ruijven, Bas; van Vuuren, Detlef P
Abstract: The role of energy in social and economic development is recognised by sustainable development goal 7 that targets three aspects of energy access: ensure universal access to affordable, reliable and modern energy services, substantially increase the share of renewable energy, and double the global rate of improvement in energy efficiency. With the projected increase in population, income and energy access in sub-Saharan Africa, demand for energy services is expected to increase. This increase can be met through increasing the supply while at the same time improving households' energy efficiency. In this paper, we explore the interactions between the three SDG7 targets by applying two integrated assessment models, IMAGE and MESSAGE, that incorporate socio-economic heterogeneity of the end-user. The results of the study depict the synergistic relationships between the three SDG7 objectives. Relative to pursuing only the universal access target, integration of all three targets could (a) reduce residential final energy consumption by up to 25%, enabling the use of mini-grid and stand-alone systems to provide better energy services, (b) cut annual energy-use-related residential emissions by a third, and (c) lower energy related investments by up to 30% to save scarce finance.